Preliminary study on metabolite differences between two obesity syndromes based on Q Exactive liquid chromatography–tandem mass spectrometry metabolomics - Ye Jing; Xiaoxuan Xu; Yanhong Wang; Xue Qu; Yunlong Guo; Ao Guo; Yulin Dai; Yangyang Liu; Hao Yue (PLoS ONE, 2025)
Background According to traditional Chinese medicine, based on the pathogenesis, clinical manifestation, and treatment, obesity can be classified into two broad types, namely, “shi obesity” and “xu obesity.” The aim of this study was to explore the differences in metabolite levels between these two types of obesity. Methods Q Exactive liquid chromatography–tandem mass spectrometry was used to analyze the metabolites in the sera of 30 healthy adults, 30 adults with shi obesity, and 30 adults with xu obesity. Possible metabolic pathways associated with biological alterations were identified using the Human Metabolome Database and Kyoto Encyclopedia of Genes and Genomes analyses. Results Fifteen important potential biomarkers were identified, 14 of which were upregulated. Furthermore, the biomarkers phenylalanine, L-tyrosine, glycerophosphocholine, and LysoPC(O-18:0/0:0) were significantly correlated with both shi and xu obesity. Of note, L-tyrosine and glycerophosphocholine were screened and used as potential biomarkers of shi and xu obesity for the first time. Conclusion This study verified the differences in serum metabolites associated with shi and xu obesity, demonstrating potential therapeutic strategies for the two types.